DETEKSI KESEHATAN GIGI DAN MULUT SERTA TELINGA ANAK USIA SEKOLAH - Purnamawati, Iga Dewi; Safitriani, Indah; Wibowo, Agus (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Good growth and development are described by the condition of healthy teeth and mouth and ears, for this reason, it is important to carry out an examination of the child's teeth, mouth and ears to prevent caries problems or cavities and obturous teeth. Dental caries problems until a hole occurs will interfere with the child's activities to learn, complaints of toothache will make the child absent and decrease appetite, while the accumulation of serum in the ear canal can cause hearing loss which results in reducing the child's school performance. This community service activity aims to provide health services in the form of dental and oral and ear examinations for students of SDN 01 cibubur grades 1 to 6 with a total of 763 students. This service activity is carried out for one day in the form of direct observation of the teeth and mouth and ears. The examination was divided into four groups consisting of puskesmas officers, lecturers and students. This community service activity received 247 (32.37 %) students experiencing dental caries, and a buildup of serum in both ears of 205 (26.87 %) students out of a total number of 763 students. The problem of caries and the accumulation of serumen experienced by school children requires follow-up by puskesmas and prevention for students who are still good, for this reason, further activities of community service will be planned in the form of education to the students of SDN 01 Cibubur through counseling on how to maintain healthy teeth, mouth and ears.